2021
DOI: 10.2147/ijgm.s343039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognosis and Risk of Death by Neutrophil/Lymphocyte Ratio, C-Reactive Protein/Albumin Ratio and Plasma D-Dimer in Patients with Pulmonary Thromboembolism

Abstract: To investigate the relationship between neutrophil/lymphocyte ratio, C-reactive protein/albumin ratio, plasma D-dimer and prognosis in patients with pulmonary thromboembolism, and to evaluate the risk of death. Methods: We retrospectively analyzed peripheral hematology and coagulation-related indicators of 362 pulmonary thromboembolism patients and 32 normal people, and the differences between the patients and control group and between good and poor prognosis groups were compared. And we analyzed and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…It was found that there was significant difference in the level of D-dimer immediately after APE between the high-risk group and low-risk group (P < 0.05). The results of logistic binary regression analysis showed that D-Dimer (or = 1.95% confidence interval 1.0 ~ 1.0, P = 0.006) was one of the independent risk factors for predicting the severity of APE patients in ICU ward, which was similar to the results of previous domestic related studies [Bi 2021;Shan 2021].…”
Section: E194supporting
confidence: 86%
“…It was found that there was significant difference in the level of D-dimer immediately after APE between the high-risk group and low-risk group (P < 0.05). The results of logistic binary regression analysis showed that D-Dimer (or = 1.95% confidence interval 1.0 ~ 1.0, P = 0.006) was one of the independent risk factors for predicting the severity of APE patients in ICU ward, which was similar to the results of previous domestic related studies [Bi 2021;Shan 2021].…”
Section: E194supporting
confidence: 86%
“… 17 Inflammation can lead to the high expression of hepcidin, which can lead to the inability of the body to use iron and lead to anemia. 9 The values of WBC, NE and SII in the good prognosis group were significantly lower than those in the poor prognosis group, suggesting that the inflammatory response and immune function were abnormal in tumor-related PTE patients. This may explain why the NLR and CAR in the good prognosis group of tumor-related PTE patients were significantly lower than those in the poor prognosis group, which is consistent with the results reported in the literature.…”
Section: Discussionmentioning
confidence: 83%
“…This may explain why the NLR and CAR in the good prognosis group of tumor-related PTE patients were significantly lower than those in the poor prognosis group, which is consistent with the results reported in the literature. 9 , 18–20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be determined in a cheap and easily available way. Recent studies showed an increase in the blood level of neutrophils in patients with PTE [9,10]. Also, cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglyceride (TG) are found to be associated with the incidence and prognosis of venous thromboembolism (VTE) and PTE [11][12][13].…”
Section: Introductionmentioning
confidence: 99%